Appropriate Work Schedule Management and Social Support Among Nurse Colleagues Function as Crucial Factors in Reducing Work Fatigue - Nur, Fauziah Yasmin; Girsang, Ermi; Nasution, Ali Napiah (FORIKES, 2025)
Nurse burnout is a significant issue affecting the quality of care and patient safety. This study aimed to analyze factors associated with nurse burnout in the inpatient ward of Royal Prima Medan General Hospital in 2025. The study used a cross-sectional design. The sample consisted of 138 nurses selected using total sampling technique according to the inclusion criteria. The variables studied included length of service, work shift, work environment, and coworker support. Data were obtained through the Subjective Self Rating Test (SSRT) questionnaire and analyzed multivariately using logistic regression. The results showed that most nurses were female (90.6%), under 36 years old (85.5%), and D3 Nursing graduates (73.9%). The majority experienced moderate levels of burnout (84.8%). Multivariate analysis showed that work shifts were the most dominant risk factor with an odds ratio of 8.506 (p=0.002), while coworker support had a protective effect with an odds ratio of 0.085 (p=0.000). As conclusion, these findings confirm that appropriate work schedule management and social support among nurse colleagues are crucial for reducing work fatigue. Hospitals are advised to strengthen healthy shift rotation programs and develop a supportive work culture to maintain nurse well-being and patient safety.Keywords: nurses; work fatigue; coworker support; work environment; work shifts